Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery
By preparing lithium iron phosphate positive electrode materials with specific structures and properties, combined with gasification and pore-making technology of carbon source, the problem of poor agglomeration behavior of lithium iron phosphate positive electrode materials is solved, and the high specific capacity and cycle stability of the battery are achieved.
Patent Information
- Application Number
- CN202510008478.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Due to its crystal structure, lithium iron phosphate positive electrode material has a low ion diffusion rate and conductivity, resulting in poor agglomeration behavior and affecting the uniformity and cycling stability of the battery.
By preparing a lithium iron phosphate positive electrode material including primary particles and secondary particles, the secondary particles are agglomerated from primary particles, satisfying the specific Fischer particle size, specific surface area particle size and relative density range, combined with different gasification temperatures The carbon source is gasified to create pores during the calcination process to inhibit particle agglomeration.
The good dispersion of lithium iron phosphate positive electrode material, low agglomeration degree and high compaction density are achieved, resulting in uniform surface density of the positive electrode sheet and high peel strength, and the battery has a high specific capacity and cycle stability.
Smart Images

Figure CN119400857A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium iron phosphate is one of the most competitive cathode active materials for lithium-ion batteries on the market. Compared with lithium cobalt oxide and ternary cathode materials, it has a longer life and better safety performance. In addition, lithium iron phosphate has a capacity of 170mAh·g -1 Theoretical specific capacity and platform discharge voltage of 3.4V make it have considerable energy density.
[0003] However, due to its crystal structure, lithium iron phosphate cathode materials have a low ion diffusion rate and conductivity. In the prior art, nano-sizing, coating, doping and other methods are usually used to improve the Li + Diffusion rate and conductivity. However, these measures have led to or affected the agglomeration behavior of lithium iron phosphate positive electrode materials to a certain extent. For example, the smaller the particle size of the positive electrode material, the more the shape deviates from the standard sphere, and the wider the distribution, the easier it is for the positive electrode material to agglomerate. For example, when the coating layer is a carbon material, if the carbon material is distributed in an island shape on the surface of the active material, the surface roughness of the positive electrode material will increase, thereby enhancing the interaction force between the particles, which is conducive to particle agglomeration. For example, the preparation process has an effect on the surface chemical properties of the obtained lithium iron phosphate positive electrode material, thereby affecting the interaction between the particles. The appearance of agglomerates causes scratches and particles to be extremely obvious during the positive electrode coating process, and also causes uneven surface density of the electrode sheet, making it difficult to maintain the uniformity of the positive electrode sheet, thus affecting the consistency of the battery.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method thereof and a lithium ion battery.
[0006] The present invention is achieved in that: In a first aspect, the present invention provides a lithium iron phosphate positive electrode material, which includes primary particles and secondary particles, wherein the secondary particles are formed by agglomeration of primary particles, and the lithium iron phosphate positive electrode material satisfies =5~40 and ρ%=50%~90%, wherein the FSSS refers to the Feasibility Study particle size of the lithium iron phosphate positive electrode material, in μm; the D BET It refers to the specific surface area particle size of the lithium iron phosphate positive electrode material, in μm; ρ%=1-H%, ρ% refers to the relative density of the secondary particles, and H% refers to the porosity of the secondary particles.
[0007] In an optional embodiment, the DBET is the particle size of the lithium iron phosphate positive electrode material measured and calculated by nitrogen adsorption-desorption method, , wherein the BET refers to the specific surface area of the lithium iron phosphate positive electrode material, and the value range of the BET satisfies ≤20m 2 / g, Refers to the true density of lithium iron phosphate positive electrode material. The value range of is 3.3~3.6 g / cm³.
[0008] In an optional embodiment, the FSSS is an average particle size of the lithium iron phosphate positive electrode material measured by a steady-flow air permeation method, and the value range of the FSSS satisfies 0.4-5 μm; And / or, the agglomeration degree N of the lithium iron phosphate positive electrode material is less than 25000, wherein the agglomeration degree ; And / or, the compaction density of the lithium iron phosphate positive electrode material is 1.9-3.0 g / cm 3 .
[0009] In an optional embodiment, the lithium iron phosphate positive electrode material satisfies =10~30; And / or, the secondary particles of the lithium iron phosphate positive electrode material satisfy ρ%=50%~70%; And / or, the lithium iron phosphate positive electrode material satisfies a degree of agglomeration N of 200 to 12000; And / or, the lithium iron phosphate positive electrode material satisfies FSSS=1~2.5μm; And / or, the lithium iron phosphate positive electrode material satisfies the BET range of 9 to 15 m 2 / g.
[0010] In an optional embodiment, the lithium iron phosphate positive electrode material comprises an active material matrix and a carbon material, and the general formula of the active material matrix is Li 1-x A x Fe 1-y M y (PO 4-z )D z , wherein A is selected from one or more of Na and Mg; M is selected from one or more of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D is selected from one or more of F, S, N and Cl; 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.1; the mass of the carbon material is 1%~5% of the mass of the lithium iron phosphate positive electrode material.
[0011] In a second aspect, the present invention provides a method for preparing a lithium iron phosphate positive electrode material as described in any one of the aforementioned embodiments, comprising: Mixing iron phosphate and lithium salt as materials, and mixing the materials with carbon sources having different gasification temperatures to obtain a precursor; The precursor is calcined in stages under an inert atmosphere, and then crushed, sieved, and demagnetized to obtain a lithium iron phosphate positive electrode material.
[0012] In an optional embodiment, the step of mixing the iron phosphate and the lithium salt includes at least one of characteristics I to IV; Feature I: Before the iron phosphate is mixed with the lithium salt, the iron phosphate is first added to a gas flow pulverizing device for pulverization; Feature II: The lithium salt is at least one of lithium carbonate, lithium oxalate and lithium acetate; Feature III: When the iron phosphate and the lithium salt are mixed, a dopant is further added, wherein the dopant is at least one of a salt, an oxide and a hydroxide of a doping element; Feature IV: The iron phosphate and the dopant are added according to a stoichiometric ratio.
[0013] In an optional embodiment, the carbon sources with different gasification temperatures include a first carbon source with a gasification temperature of 400-600°C, a second carbon source with a gasification temperature of 200-400°C, and a third carbon source with a gasification temperature of 100-200°C; The first carbon source comprises at least one of polyimide, polyphenylene ether and polyetherimide; The second carbon source comprises at least one of glucose, polyethylene glycol, starch, sucrose, maltose, cellulose, chitosan, polyacrylonitrile, benzyl alcohol and glycerol; The third carbon source includes at least one of phenol, ethylene glycol, propylene glycol, butylene glycol, isopropanol, sorbitol, erythritol, fructose, malic acid, citric acid and salicylic acid.
[0014] In an optional embodiment, the step of mixing the material with a carbon source having a different gasification temperature includes at least one of characteristics V to IX; Feature V: The material and the carbon source with different gasification temperatures are mixed in a gas flow milling device, and a gas flow is introduced during the mixing, the pressure of the gas flow is 0.5-1.5 MPa, and the temperature is 25-120° C.; the total mixing time is 15-60 min; Feature VI: Before the carbon sources with different gasification temperatures are mixed with the material, they are first prepared into a carbon source solution with a mass percentage concentration of 10% to 30%, and then the carbon source solution is atomized and then mixed with the material, wherein the atomization pressure is 0.1 to 1.5 MPa; Feature VII: The material is first mixed with the first carbon source, then mixed with the second carbon source, and finally mixed with the third carbon source; Feature VIII: The total mass of the carbon sources with different gasification temperatures is 15% to 25% of the mass of the material; Feature IX: When the material is mixed with carbon sources having different gasification temperatures, the mass ratio of the first carbon source, the second carbon source and the third carbon source is 0~15:2.5~15:2.5~10.
[0015] In an optional embodiment, the staged calcination includes a first stage, a second stage and a third stage, wherein the first stage is heated to 180-220°C at a speed of 1-2°C / min and kept warm for 1-2 hours; the second stage is heated to 380-420°C at a speed of 2-3°C / min and kept warm for 2-4 hours; the third stage is heated to 650-750°C at a speed of 4-6°C / min and kept warm for 4-8 hours.
[0016] In a third aspect, the present invention provides a lithium-ion battery, comprising the lithium iron phosphate positive electrode material as described in any one of the aforementioned embodiments or the lithium iron phosphate positive electrode material prepared by the method for preparing the lithium iron phosphate positive electrode material as described in any one of the aforementioned embodiments.
[0017] The present invention has the following beneficial effects: (1) The present invention provides a method that satisfies =5~40 and ρ%=50%~90% lithium iron phosphate positive electrode material, the lithium iron phosphate positive electrode material has good dispersibility, low agglomeration degree and high compaction density; the positive electrode sheet prepared using the positive electrode active material has the characteristics of uniform surface density and high peel strength, so the prepared battery has high specific capacity and cycle stability.
[0018] (2) The preparation method of the lithium iron phosphate positive electrode material provided by the present invention utilizes carbon sources with different gasification temperatures to perform gasification and pore formation at different calcination stages, so that the material particles are loosely bonded and the adhesion and agglomeration between the particles are inhibited, thereby making the agglomeration degree of the obtained positive electrode material low. The preparation method provided by the present invention can obtain =5~40 and ρ%=50%~90% lithium iron phosphate positive electrode material, the lithium iron phosphate positive electrode material has good dispersibility, low agglomeration degree and high compaction density, the positive electrode sheet prepared therefrom has the characteristics of uniform surface density and high peeling strength, so the prepared battery has high specific capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 This is a SEM image of the lithium iron phosphate positive electrode material provided in Example 1 of the present invention; Figure 2 This is a SEM image of the lithium iron phosphate positive electrode material provided in Example 8 of the present invention; Figure 3 This is a SEM image of the lithium iron phosphate positive electrode material provided in Comparative Example 4 of the present invention; Figure 4 This is a Raman spectrum of the lithium iron phosphate positive electrode material provided in Example 1 and Example 4 of the present invention. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0022] A lithium iron phosphate positive electrode material, comprising primary particles and secondary particles formed by agglomeration of the primary particles, wherein the lithium iron phosphate positive electrode material satisfies =5~40 and ρ%=50%~90%, where FSSS refers to the Feasibility Study of LiFePO4 cathode material, in μm; D BET It refers to the specific surface area particle size of lithium iron phosphate positive electrode material, in μm; ρ%=1-H%, ρ% refers to the relative density of secondary particles, and H% refers to the porosity of the secondary particles.
[0023] The present invention provides a method that satisfies both The lithium iron phosphate positive electrode material with ρ% and ρ% in a specific range has good dispersibility, low agglomeration degree and high compaction density. The positive electrode sheet prepared with it as the positive electrode active material has the characteristics of uniform surface density and high peeling strength. Therefore, the prepared battery has higher specific capacity and cycle stability.
[0024] Specifically, It reflects the ratio of secondary particle size to primary particle size. The better the dispersion of lithium iron phosphate cathode material and the lower the degree of agglomeration, The lithium iron phosphate positive electrode material provided by the present invention The range is 5~40, Too high or too low will lead to a decrease in the tap density of the positive electrode material, which in turn leads to a decrease in the specific capacity of the lithium iron phosphate positive electrode material battery. Too high indicates that the lithium iron phosphate positive electrode material has a high degree of agglomeration, and there are large pores between the agglomerated secondary particles, resulting in a low tap density; too low indicates that the lithium iron phosphate positive electrode material is mainly dispersed primary particles. Since the porosity of secondary particles (agglomerates) is usually lower than the porosity of primary particle powder in the tapped state, too low agglomeration will also cause a decrease in tap density.
[0025] In some embodiments, The value range of is 10~30, for example, it can be any one of 10, 12, 15, 18, 20, 22, 25, 28, 30 or a range value between any two of them.
[0026] In some embodiments, the value range of FSSS satisfies 0.4~5μm, for example, it can be any one of 0.4μm, 0.5μm, 0.8μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or a range value between any two of them; in some other embodiments, the value range of FSSS satisfies 1~2.5μm.
[0027] The Fisher particle size distribution (FSSS) is the average particle size of the lithium iron phosphate positive electrode material measured by the steady-flow air permeation method. The mechanism is: use constant pressure and constant flow air to pass through the powder sample tube, and calculate the specific surface area and average particle size of the powder according to the formula by measuring the gas pressure difference. Since the airflow is constant pressure and constant flow, the measured specific surface area is the external specific surface area of the powder, so the average particle size obtained can reflect the particle size of the agglomerate.
[0028] Specific surface area particle size ( ) is the volume area average diameter, which is defined as the specific surface area of particles with this diameter, equal to the average specific surface area of all particles; it is tested and calculated by the nitrogen adsorption and desorption method, and its mechanism is: by measuring the nitrogen adsorption amount of the powder sample at different pressures, the specific surface area (BET) of the powder is calculated according to the formula. Since the airflow is a pressurized airflow and the collected data is the gas adsorption amount, the measured specific surface area is the total specific surface area of the powder. Therefore, the particle size calculated by the BET specific surface area can reflect the particle size of the primary particles. The calculation formula is as follows: , where BET refers to the specific surface area of lithium iron phosphate cathode material, in m 2 / g, Refers to the true density of lithium iron phosphate positive electrode material, unit is g / cm 3 .according to definition, ,Right now ;at the same time, ;therefore .
[0029] In some embodiments, the value range of BET satisfies ≤20m 2 / g; In some embodiments, the BET value range is 9 to 15m 2 / g, for example, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g or any range between two thereof; in some embodiments, The value range of satisfies 3.3~3.6 g / cm³, for example, it can be any one of 3.3 g / cm³, 3.4 g / cm³, 3.5 g / cm³, 3.6 g / cm³ or a range value between any two of them.
[0030] The relative density of lithium iron phosphate secondary particles refers to the ratio of its apparent density to the true density of lithium iron phosphate. The apparent density refers to the ratio of the mass of the material to the apparent volume. The apparent volume is the sum of the real volume and the pore volume, that is, the apparent volume is the sum of the solid volume and the pore volume of lithium iron phosphate. The true density refers to the actual mass of the solid material per unit volume in an absolutely dense state, that is, the density after removing the internal pores. The relative density of secondary particles can be calculated by the porosity (H%) of the secondary particles, that is, =1-H%. The higher the porosity of the secondary particles, the lower the relative density, indicating that the structure of the secondary particles is looser, the easier it is to disperse, the higher the compaction density, and the further prepared positive electrode sheet has uniform surface density and high peel strength, and thus has higher specific capacity and cycle stability. The value is 50% to 90%. If it is too high, the secondary particles will be difficult to disperse, and if it is too low, the tap density of the lithium iron phosphate positive electrode material will be reduced. In some embodiments, The value ranges from 50% to 70%.
[0031] In some embodiments, the degree of agglomeration N of the lithium iron phosphate positive electrode material is less than 25000, wherein the degree of agglomeration .
[0032] In some embodiments, the degree of agglomeration N of the lithium iron phosphate positive electrode material is 200 to 12000. The lithium iron phosphate positive electrode material meeting the agglomeration value has a better compaction density, and the prepared electrode sheet surface density is more uniform, and thus has a higher specific capacity and cycle stability.
[0033] The degree of agglomeration N reflects the number of primary particles contained in the secondary particles in the lithium iron phosphate positive electrode material. Specifically, the degree of agglomeration N= = =( ) 3 × The smaller the value of the degree of agglomeration N, the lower the degree of agglomeration and the better the uniformity of the electrode. However, if the degree of agglomeration N is too low, it indicates that the relative density of the lithium iron phosphate positive electrode material is or If it is too small, the material's tap density will be too low, resulting in a lower specific capacity.
[0034] In some embodiments, the compaction density of the lithium iron phosphate positive electrode material is 1.9-3.0 g / cm 3 , the compaction density is tested under 3T pressure.
[0035] In some embodiments, the lithium iron phosphate positive electrode material includes an active material matrix and a carbon material, and the general formula of the active material matrix is Li 1-x A x Fe 1-y M y (PO 4-z )D z , wherein A is selected from one or more of Na and Mg; M is selected from one or more of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D is selected from one or more of F, S, N and Cl; 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.1; the mass of the carbon material is 1%~5% of the mass of the lithium iron phosphate positive electrode material.
[0036] In addition, the present invention provides a method for preparing a lithium iron phosphate positive electrode material, which comprises the following steps: S1. Mix iron phosphate and lithium salt as materials.
[0037] Before the iron phosphate is mixed with the lithium salt, the iron phosphate is first added to an air flow pulverizing device for pulverization. The pulverization process can refine the iron phosphate to facilitate subsequent uniform mixing with the lithium salt.
[0038] In this embodiment, the lithium salt includes but is not limited to at least one of lithium carbonate, lithium oxalate and lithium acetate; when the iron phosphate is mixed with the lithium salt, a dopant may be added according to actual product requirements, and the iron phosphate and the dopant are added according to a stoichiometric ratio. The dopant includes but is not limited to at least one of a salt, oxide and hydroxide of a doping element.
[0039] S2. Mixing the material with carbon sources having different gasification temperatures to obtain a precursor.
[0040] Before mixing with the material, the carbon sources with different gasification temperatures are first prepared into a carbon source solution with a mass percentage concentration of 10% to 30%, and then the carbon source solution is atomized and then mixed with the material, wherein the atomization pressure is 0.1 to 1.5 MPa; the material and the carbon sources with different gasification temperatures are mixed in an air flow pulverizing device, and an air flow is introduced during mixing, and the air flow pressure is 0.5 to 1.5 MPa and the temperature is 25 to 120°C; the total mixing time is 15 to 60 minutes.
[0041] In this embodiment, the carbon sources with different gasification temperatures include a first carbon source with a gasification temperature of 400~600°C, a second carbon source with a gasification temperature of 200~400°C, and a third carbon source with a gasification temperature of 100~200°C; the material is first mixed with the first carbon source, then with the second carbon source, and finally with the third carbon source; the total mass of the carbon sources with different gasification temperatures is 15%~25% of the mass of the material; when the material is mixed with the carbon sources with different gasification temperatures, the mass ratio of the first carbon source, the second carbon source and the third carbon source is 0~15:2.5~15:2.5~10, wherein when the mass of the first carbon source is 0, it means that the carbon source only includes the second carbon source and the third carbon source.
[0042] Among them, the first carbon source includes but is not limited to at least one of polyimide, polyphenylene ether and polyetherimide; the second carbon source includes but is not limited to at least one of glucose, polyethylene glycol, starch, sucrose, maltose, cellulose, chitosan, polyacrylonitrile, benzyl alcohol and glycerol; the third carbon source includes but is not limited to at least one of phenol, ethylene glycol, propylene glycol, butylene glycol, isopropanol, sorbitol, erythritol, fructose, malic acid, citric acid and salicylic acid.
[0043] Compared with the second or third carbon source, the first carbon source has the characteristics of strong molecular chain rigidity, high degree of conjugation, and large amount of solid residue after decomposition. Therefore, its degree of graphitization is relatively high, which is beneficial to improving the conductivity of the positive electrode material. On the one hand, since the first carbon source is more hydrophobic than the second or third carbon source, it can be better coated on the surface of the material particles after being mixed with the material in advance. On the other hand, prior mixing can make the conductive carbon network formed by calcination tightly distributed on the surface of the lithium iron phosphate particles.
[0044] S3. The precursor is calcined in stages under an inert atmosphere, and then crushed, sieved, and demagnetized to obtain a lithium iron phosphate positive electrode material.
[0045] The staged calcination includes the first stage, the second stage and the third stage. The first stage is heated to 180-220°C at 1-2°C / min and kept warm for 1-2 hours; the second stage is heated to 380-420°C at 2-3°C / min and kept warm for 2-4 hours; the third stage is heated to 650-750°C at 4-6°C / min and kept warm for 4-8 hours.
[0046] The lithium iron phosphate positive electrode material can be widely used in the preparation of batteries, and the prepared batteries have excellent electrochemical performance. In this regard, the present invention also provides a lithium ion battery, which includes the lithium iron phosphate positive electrode material.
[0047] The battery provided by the present invention may generally include a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The method of preparing a battery should be known to those skilled in the art. For example, the positive electrode sheet, the separator, and the negative electrode sheet may each be a sheet body, so that they can be cut into a target size and stacked in sequence, and can also be wound to a target size to form a battery cell, and can be further combined with an electrolyte to form a battery.
[0048] In the battery provided by the present invention, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector, and the negative electrode active material layer generally includes a negative electrode active material. The negative electrode active material can be various materials suitable for negative electrode active materials of lithium ion batteries in the art, for example, it can include but is not limited to graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium, etc. One or more combinations. Among them, graphite can be selected from a combination of one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from a combination of one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; tin-based materials can be selected from a combination of one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials suitable for use as a negative electrode current collector of a lithium ion battery in the art. For example, the negative electrode current collector can be, but is not limited to, metal foil, etc., and more specifically, it can be, but is not limited to, copper foil, etc.
[0049] In the battery provided by the present invention, the isolation membrane can be any material suitable for lithium-ion battery isolation membranes in the art, for example, it can include but is not limited to a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0050] In the battery provided by the present invention, the electrolyte can be any electrolyte suitable for lithium-ion batteries in the art. For example, the electrolyte generally includes an electrolyte and a solvent. The electrolyte generally includes a lithium salt, etc. More specifically, the lithium salt can be an inorganic lithium salt and / or an organic lithium salt, etc. The lithium salt can be selected from a combination of one or more of LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiN(CF3SO2)2 (abbreviated as LiTFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), and LiBF2C2O4 (abbreviated as LiDFOB). For another example, the concentration of the electrolyte can be between 0.8 mol / L and 1.5 mol / L. The solvent may be any solvent suitable for the electrolyte of a lithium ion battery in the art. The solvent of the electrolyte is usually a non-aqueous solvent, preferably an organic solvent, and may specifically include but is not limited to ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, etc., or a combination of one or more of their halogenated derivatives.
[0051] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0052] The present invention provides lithium iron phosphate positive electrode materials as shown in Table 1, Table 2 and Table 3, and detects them.
[0053] Button cell battery assembly includes the following steps: (1) Slurry preparation The binder PVDF was added to part of the NMP and stirred in a double planetary mixer at an orbital speed of 80 rpm, an autorotational speed of 4500 rpm, and a stirring time of 120 min to obtain a glue solution with a solid content of 7%; acetylene black was added to the glue solution and stirred at an orbital speed of 80 rpm, an autorotational speed of 4500 rpm, and a stirring time of 60 min to obtain a conductive slurry; lithium iron phosphate positive electrode material and the remaining NMP were added to the conductive slurry at an orbital speed of 80 rpm, an autorotational speed of 6500 rpm, and a stirring time of 90 min, and then stirred at an autorotational speed of 15 rpm for 30 min for defoaming to obtain a positive electrode slurry with a solid content of 65%.
[0054] The mass ratio of lithium iron phosphate positive electrode material, acetylene black and PVDF is 97.2:0.8:2. The average particle size of acetylene black is 40nm and the specific surface area is 65m 2 / g.
[0055] (2) Electrode preparation The positive electrode slurry was coated on the aluminum foil substrate using a double-sided reciprocating coater and dried to obtain the positive electrode sheet. In the rolling process, the main roller temperature was set to 40°C and the main roller pressure was controlled to make the compaction density of the electrode sheet 2.55g / cm 3 .
[0056] (3) Button battery assembly The negative electrode is a lithium sheet, the separator is a polypropylene porous membrane, and the electrolyte is prepared by dissolving 1 mol LiPF6 in a mixed solvent of 1L EC and DMC (volume ratio 1:1). The positive electrode, negative electrode, electrolyte, and separator are assembled into a battery in an argon-protected glove box.
[0057] Test methods include: (1) Carbon content: measured using a high-frequency infrared carbon and sulfur analyzer in accordance with YS / T 1028.4-2015.
[0058] (2) True density (ρ LFP ): Measured in accordance with the helium method of GB / T 24203-2024.
[0059] (3) Fisher's particle size specification (FSSS): measured in accordance with GB / T 3249-2022.
[0060] (4) Specific surface area (BET): measured using a Micromeritics physical adsorption instrument according to the BET method of GB / T 19587-2017, and then Calculated , and then further calculate to get .
[0061] (5) Relative density of secondary particles (ρ%): All or part of the secondary particles are separated from the sample to be tested, and then their porosity (H%) is tested. The relative density of the secondary particles is calculated by ρ%=1-H%.
[0062] In an embodiment of the present invention, the following method is used to separate secondary particles: the sample to be tested is vibrated and sieved (the difference in the number of adjacent sieves is 10 meshes) to obtain sub-samples of multiple particle size ranges, the sub-samples of different particle size ranges are separated by gravity sedimentation (water medium), the precipitate is dried at room temperature to obtain the secondary particles of the sub-sample, and then the secondary particles of all sub-samples are combined.
[0063] In the embodiment of the present invention, a scanning electron microscope (SEM) is used to observe and calculate the porosity of the secondary particles: the magnification is adjusted until there is only one complete cross-section of the secondary particle in the view and a SEM photo is taken, and then the SEM photo is analyzed by Image-Pro Plus software and the porosity is calculated, porosity = (sum of the areas of the pores of the secondary particles in the cross-section / cross-sectional area of the secondary particles) × 100%.
[0064] (6) The calculation formula of the degree of agglomeration N is N=( ) 3 × .
[0065] (7) Compacted density (CD): tested in accordance with GB / T 24533-2009, with the pressure end point being 3T (600 MPa).
[0066] (8) Surface density test: The surface density of the electrode is tested by X-ray fluorescence spectrometry (XRF). The electrode to be tested is cut into 20 small samples of the same size for testing to obtain the content of each element, and the mass of the lithium iron phosphate positive electrode material and its surface density are calculated. The average value is taken as the average surface density, and the standard deviation of the surface density sample is calculated.
[0067] (9) Peel strength test: The test was carried out on an Instron 3365 tensile testing machine using a 180° peel test method at a pulling speed of 60 mm / min.
[0068] (10) Electrode resistance: The test was performed using the Yuanneng Technology BER2100 multi-function electrode resistance meter. Ten different locations were tested and the average value and sample standard deviation were calculated.
[0069] (11) Electrochemical properties: The battery constant current charge-discharge and cycle performance tests were performed using the LAND battery test system. The charge-discharge voltage range was 2.5–4.2 V at 25 °C.
[0070] The test results are shown in Table 1, Table 2 and Table 3.
[0071] Table 1. General formula and parameter test statistics of different samples
[0072] Table 2. Statistics of physical properties of different samples
[0073] Table 3. Electrochemical performance test statistics of different samples
[0074] It can be seen from Table 1, Table 2 and Table 3 that the lithium iron phosphate positive electrode material of the embodiment of the present invention has a higher compaction density and better comprehensive performance than the comparative example. Less than 5 or more than 40, or If it is greater than 90%, the compaction density will be too small, thus affecting the charge and discharge specific capacity. It reflects the ratio of the particle size of secondary particles to primary particles and reflects the degree of agglomeration; It can reflect the compactness of the agglomeration of primary particles in secondary particles. If the compactness is too low, the particles are easily crushed and rearranged during compaction, or if the agglomeration is too low, it is easy to cause too much pore volume between particles, which is not conducive to improving compaction density. If the agglomeration is too high, or the compactness is too high, the secondary particles are difficult to crush during compaction, and the pore volume formed by the overlapping of large particles is too large, which is not conducive to improving compaction density. and The compaction density of the positive electrode material must be maintained within a reasonable range to achieve a high compaction density. The compaction density will affect the specific capacity and rate performance of the material, so the comparative example has poorer electrochemical performance than Example 1.
[0075] Example 2 Lithium iron phosphate positive electrode material meets =5~40 and ρ%=50%~90%, but it does not meet the range of agglomeration degree N lower than 25000. At this time, compared with other embodiments, the compaction density of the lithium iron phosphate positive electrode material is lower, resulting in lower electrode peeling strength; due to excessive agglomeration, the standard deviation of the surface density sample and the standard deviation of the pole piece resistance sample are both large, and the compaction density and specific surface area are lower, so that the lithium deintercalation speed decreases, and thus has lower rate performance and poorer cycle stability. The agglomeration degree N of the positive electrode materials in the other embodiments is lower than 25000, and the performance is good.
[0076] Compared with Example 6, Examples 1, 3, and 5 have higher compaction density; in addition, they also have the characteristics of higher peel strength of the pole piece, lower standard deviation of the surface density sample and the pole piece resistance sample, so their rate performance and capacity retention rate are higher. This shows that the comprehensive performance of the lithium iron phosphate positive electrode material is better when the preferred range of agglomeration degree is 200-12000.
[0077] Compared with Examples 1, 3, and 5, Example 4 has a lower compaction density because the degree of agglomeration of Example 4 is lower than the preferred range of 200, indicating that the degree of agglomeration of the positive electrode material is low. Due to the low degree of agglomeration, the number of primary particles is large, that is, the overall particle size is small, resulting in a low compaction density, which further affects the specific capacity of the material. Due to the low degree of agglomeration of the positive electrode material, the standard deviation of the surface density sample and the standard deviation of the pole sheet resistance sample are both low; in addition, the degree of agglomeration is low, the number of primary particles is large, that is, the overall particle size is small, and the specific surface area is large, thereby improving the adhesion of the positive electrode material coating to the current collector and improving the peel strength.
[0078] Example 1, Example 5, and Comparative Example 2 have similar chemical compositions and , but with different , comparing the performance data of the three, we can see that with The compaction density increases first and then decreases. The reason is that too large or too small agglomeration will lead to more pores between particles, thus reducing the compaction density. In similar cases, with The increase indicates that the number of primary particles contained in a single secondary particle increases, which increases the overall compaction density; but further increase , indicating that the larger the particle size of the secondary particles or the smaller the particle size of the primary particles that make up the secondary particles, both of which will break the gradation balance and cause the compaction density to decrease; the compaction density has a great influence on the specific capacity of the lithium iron phosphate positive electrode material. The larger the value, the larger the standard deviation of the surface density of the electrode, the smaller the peel strength, the larger the electrode resistance, and the larger the standard deviation of the electrode resistance. Finally, Example 1 has excellent electrochemical performance, indicating that the lithium iron phosphate positive electrode It should be maintained within a certain range so that its degree of agglomeration N is maintained within a certain range.
[0079] Example 2, Example 6, Example 7, and Comparative Example 3 have similar chemical compositions and , but with different , comparing the performance data of the three, we can see that with The compaction density increases first and then decreases. The reason is that the secondary particles with higher relative density can increase the overall compaction density on the one hand, and on the other hand, they are difficult to be crushed during the compaction process. The larger secondary particles overlap with each other to form more pores, which leads to a decrease in compaction density. In addition, as As the agglomeration degree N of the lithium iron phosphate cathode material increases, the peel strength decreases; The agglomeration degree N increases, the resistance of the electrode increases, and the standard deviation of the electrode surface density sample and the standard deviation of the electrode resistance sample will increase; Finally, Example 7 has excellent electrochemical performance, indicating that the lithium iron phosphate positive electrode material Or the degree of agglomeration N should be maintained within a certain range.
[0080] In addition, the present invention also provides corresponding preparation methods of the above product embodiments and product comparison examples.
[0081] Method Example 1 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned embodiment 1, and the preparation method of this embodiment comprises the following steps: (1) Introducing air into the air flow pulverizing device to pulverize anhydrous ferric phosphate with a Dv50 of 8.52 μm to obtain anhydrous ferric phosphate with a Dv50 of 0.4-0.5 μm; (2) The anhydrous ferric phosphate obtained in step (1) is mixed with lithium carbonate as a material to prepare a first carbon source solution, a second carbon source solution and a third carbon source solution; the atomized first carbon source solution, the second carbon source solution and the third carbon source solution are successively introduced into an air flow pulverizing device using air as a medium to pulverize and coat the materials, thereby obtaining a first precursor, a second precursor and a third precursor, respectively.
[0082] Anhydrous ferric phosphate and lithium carbonate are mixed according to n(Fe):n(Li)=1:1.05.
[0083] The first carbon source solution is a polyimide DMF solution with a concentration of 10 wt %; the second carbon source solution is a glucose aqueous solution with a concentration of 20 wt %; and the third carbon source solution is an ethylene glycol ethanol solution with a concentration of 10 wt %.
[0084] The feed ratio of the material, the first carbon source solution, the second carbon source solution and the third carbon source solution is 10g:5g:2.5g:5g.
[0085] The pressure of the air flow is 1±0.1MPa; when the material is mixed with the first carbon source solution, the air flow temperature is 120°C, and the mixing time is 20min; when the first precursor is mixed with the second carbon source solution, the air flow temperature is 100°C, and the mixing time is 15min; when the second precursor is mixed with the third carbon source solution, the air flow temperature is 80°C, and the mixing time is 15min.
[0086] The atomization pressure is 1MPa.
[0087] (3) The third precursor is placed in a rotary kiln and calcined in three stages under a nitrogen atmosphere, and then mechanically crushed, sieved, and demagnetized to obtain a lithium iron phosphate positive electrode material.
[0088] The three-stage calcination includes: the first stage is heated to 200°C at 1°C / min and kept at this temperature for 1 hour; the second stage is heated to 400°C at 2°C / min and kept at this temperature for 3 hours; the third stage is heated to 700°C at 5°C / min and kept at this temperature for 6 hours.
[0089] Method Example 2 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned embodiment 2, and the preparation method of this embodiment comprises the following steps: (1) Dry-mixing anhydrous ferric phosphate with a Dv50 of 8.52 μm with lithium acetate, titanyl sulfate, a first carbon source, a second carbon source, and a third carbon source to obtain a material, and grinding and crushing the material in a ball mill to obtain a precursor, and controlling the Dv50 of the precursor to be 0.4-0.5 μm.
[0090] Anhydrous ferric phosphate, titanyl sulfate and lithium acetate are mixed according to n(Fe):n(Ti):n(Li)=0.986:0.014:1.05.
[0091] The first carbon source is polyimide; the second carbon source is glucose; and the third carbon source is erythritol.
[0092] The total mass of anhydrous ferric phosphate, lithium acetate, titanyl sulfate, the first carbon source, the second carbon source, and the third carbon source are fed in a ratio of 10 g: 0.7 g: 0.7 g: 0.7 g.
[0093] Ball milling conditions: frequency is 30 Hz, 1 mm zirconia beads are used for ball milling, the volume ratio of the beads to the material is 1:1, the rotation speed is 600 rpm, the ball milling time is 3 h, and the temperature is room temperature.
[0094] (2) The precursor is placed in a rotary kiln and calcined in three stages under a nitrogen atmosphere, and then the lithium iron phosphate positive electrode material is obtained through mechanical crushing, screening and demagnetization.
[0095] The three-stage calcination includes: the first stage is heated to 200°C at 1°C / min and kept at this temperature for 1 hour; the second stage is heated to 400°C at 2°C / min and kept at this temperature for 2 hours; the third stage is heated to 700°C at 5°C / min and kept at this temperature for 8 hours.
[0096] Method Example 3 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned embodiment 3, and the preparation method of this embodiment comprises the following steps: The difference from method embodiment 1 is that: The medium of the air flow pulverizing device is nitrogen; In step (2), lithium oxalate is used as a lithium source; sodium fluoride is also added to the material, and anhydrous ferric phosphate, sodium fluoride and lithium oxalate are mixed according to n(Fe):n(Na):n(Li)=0.988:0.002:1.05.
[0097] The first carbon source solution is a 10wt% toluene solution of polyphenylene ether; the second carbon source solution is a 20wt% ethanol solution of polyethylene glycol-400; the third carbon source solution is a 10wt% ethanol solution of fructose; the feed ratio of the material, the first carbon source solution, the second carbon source solution, and the third carbon source solution is 10:2.5:2.5:7.5.
[0098] The pressure of the air flow is 0.8±0.1MPa; when the material is mixed with the first carbon source solution, the air flow temperature is 120°C, and the mixing time is 15min; when the first precursor is mixed with the second carbon source solution, the air flow temperature is 70°C, and the mixing time is 15min; when the second precursor is mixed with the third carbon source solution, the air flow temperature is 70°C, and the mixing time is 30min.
[0099] The atomization pressure is 0.8MPa.
[0100] The three-stage calcination in step (3) includes: the first stage is heated to 200°C at 1°C / min and kept at this temperature for 2 hours; the second stage is heated to 400°C at 2°C / min and kept at this temperature for 2 hours; the third stage is heated to 650°C at 5°C / min and kept at this temperature for 5 hours.
[0101] Method Example 4 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned embodiment 4, and the preparation method of this embodiment comprises the following steps: The difference from method embodiment 1 is that: In step (2), lithium oxalate is used as the lithium source; the first carbon source is not added, the second carbon source solution is a 20 wt % polyethylene glycol-400 ethanol solution; the third carbon source solution is a 10 wt % ethylene glycol ethanol solution; the feed ratio of the material, the second carbon source solution, and the third carbon source solution is 10:5:8.
[0102] The pressure of the air flow is 1.5±0.1 MPa; when the material is mixed with the second carbon source solution, the air flow temperature is 80°C and the mixing time is 30 min; when the second precursor is mixed with the third carbon source solution, the air flow temperature is 80°C and the mixing time is 20 min.
[0103] The atomization pressure is 1MPa.
[0104] The three-stage calcination in step (3) includes: the first stage is heated to 200°C at 1°C / min and kept at this temperature for 2 hours; the second stage is heated to 400°C at 2°C / min and kept at this temperature for 4 hours; the third stage is heated to 650°C at 5°C / min and kept at this temperature for 5 hours.
[0105] Method Example 5 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned embodiment 5, and the preparation method of this embodiment comprises the following steps: The difference from method embodiment 1 is that: In step (2), the first carbon source solution is a 16 wt % polyimide DMF solution; the second carbon source solution is a 10 wt % aqueous solution of amylose; the third carbon source solution is a 20 wt % citric acid ethanol solution; and the feed ratio of the material, the first carbon source solution, the second carbon source solution, and the third carbon source solution is 10:6.25:2.5:1.25.
[0106] The atomization pressure is 0.5MPa.
[0107] The three-stage calcination in step (3) includes: the first stage is to heat up to 200°C at 2°C / min and keep it at that temperature for 2 hours; the second stage is to heat up to 400°C at 2°C / min and keep it at that temperature for 2 hours; the third stage is to heat up to 750°C at 5°C / min and keep it at that temperature for 5 hours.
[0108] Method Example 6 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned embodiment 6, and the preparation method of this embodiment comprises the following steps: (1) Anhydrous iron phosphate with a Dv50 of 8.52 μm is mixed with lithium carbonate, titanyl sulfate, a second carbon source, and a third carbon source to obtain a material, and the material is placed in a ball mill for grinding and crushing to obtain a precursor, and the Dv50 of the precursor is controlled to be 0.4-0.5 μm.
[0109] Anhydrous ferric phosphate, titanyl sulfate and lithium carbonate are mixed according to n(Fe):n(Ti):n(Li)=0.988:0.012:1.05.
[0110] The second carbon source is polyethylene glycol-400; the third carbon source is ethylene glycol.
[0111] The total mass of anhydrous ferric phosphate, lithium carbonate, titanyl sulfate, the second carbon source, and the third carbon source are fed in a ratio of 10:1.5:1.
[0112] Grinding conditions: frequency is 30 Hz, 1 mm zirconia beads are used in the ball mill, the volume ratio of the amount to the material is 1:1, the rotation speed is 600 rpm, the ball milling time is 3 h, and the temperature is room temperature.
[0113] (2) The precursor is placed in a rotary kiln and calcined in three stages under a nitrogen atmosphere, and then the lithium iron phosphate positive electrode material is obtained through mechanical crushing, screening and demagnetization.
[0114] The three-stage calcination includes: the first stage is heated to 200°C at 1°C / min and kept at this temperature for 2 hours; the second stage is heated to 400°C at 2°C / min and kept at this temperature for 2 hours; the third stage is heated to 750°C at 5°C / min and kept at this temperature for 6 hours.
[0115] Method Example 7 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned embodiment 7, and the preparation method of this embodiment comprises the following steps: The difference from method example 5 is that the material in step (2) also includes titanyl sulfate, and anhydrous ferric phosphate is mixed with titanyl sulfate and lithium carbonate according to n(Fe): n(Ti): n(Li)=0.988:0.012:1.05; the feed ratio of the material, the first carbon source solution, the second carbon source solution, and the third carbon source solution is 10:9.375:5:2.5.
[0116] Method Comparative Example 1 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned comparative example 1, and the preparation method of this comparative example comprises the following steps: (1) According to the solute:solvent ratio of 2 g:40 mL, ferrous sulfate heptahydrate, lithium hydroxide, and phosphoric acid were mixed and dispersed in a mixed solvent (the volume ratio of ethylene glycol to water was 1:1) according to n(Fe):n(Li):n(P)=3:1:1, stirred evenly, and then kept warm at 180°C for 6 h. After solid-liquid separation, the mixture was washed and dried to obtain lithium iron phosphate powder.
[0117] (2) Mixing lithium iron phosphate powder and glucose, placing them in a rotary kiln for calcination under a nitrogen atmosphere, and then mechanically crushing, screening, and demagnetizing to obtain a lithium iron phosphate positive electrode material. The calcination conditions are heating to 650°C at 5°C / min and keeping the temperature for 5 hours. The mass of the glucose is 15% of the mass of the lithium iron phosphate powder.
[0118] Method Comparative Example 2 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above-mentioned comparative example 2, and the preparation method of this comparative example comprises the following steps: (1) According to the solute:solvent ratio of 2 g:40 mL, ferrous sulfate heptahydrate, lithium hydroxide, and phosphoric acid were mixed and dispersed in a mixed solvent (the volume ratio of ethylene glycol to water was 1:1) according to n(Fe):n(Li):n(P)=3:1:1, stirred evenly, and then kept warm at 180°C for 6 h. After solid-liquid separation, the mixture was washed and dried to obtain lithium iron phosphate powder.
[0119] (2) The lithium iron phosphate powder and the mixed carbon source are mixed and placed in a ball mill for grinding and crushing to obtain a mixture.
[0120] The mixed carbon source is a mixture of polyimide, glucose and erythritol in a mass ratio of 1:1:1.
[0121] The mass of the mixed carbon source is 15% of the mass of the lithium iron phosphate powder.
[0122] Ball milling conditions: frequency is 30 Hz, 1 mm zirconia beads are used for ball milling, the volume ratio of the beads to the material is 1:1, the rotation speed is 600 rpm, the ball milling time is 3 h, and the temperature is room temperature.
[0123] (3) The mixed material is placed in a rotary kiln and calcined in three stages under a nitrogen atmosphere, and then mechanically crushed, sieved, and demagnetized to obtain a lithium iron phosphate positive electrode material. The three-stage calcination includes: the first stage is heated to 200°C at 2°C / min and kept at this temperature for 1 hour; the second stage is heated to 400°C at 2°C / min and kept at this temperature for 2 hours; the third stage is heated to 700°C at 5°C / min and kept at this temperature for 8 hours.
[0124] Method Comparative Example 3 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above comparative example 3, and the preparation method of this comparative example comprises the following steps: The difference from method example 1 is that the material in step (2) also includes titanyl sulfate, and anhydrous iron phosphate, titanyl sulfate and lithium carbonate are mixed according to n(Fe):n(Ti):n(Li)=0.986:0.014:1.05. Step (3) adopts a one-stage calcination, that is, the temperature is increased to 700°C at 2°C / min and kept at this temperature for 8h to obtain a lithium iron phosphate positive electrode material.
[0125] Method Comparative Example 4 A method for preparing a lithium iron phosphate positive electrode material, wherein the product obtained by the preparation corresponds to the product of the above comparative example 4, and the preparation method of this comparative example comprises the following steps: The difference from method example 1 is that only the second carbon source solution is added in step (2), and step (3) adopts a one-stage calcination, which specifically includes the following steps: (1) Same as in method embodiment 1; (2) The anhydrous iron phosphate obtained in step (1) is mixed with lithium carbonate as a material, and the atomized second carbon source solution is introduced into an air flow pulverizing device using air as a medium to pulverize and coat the material to obtain a precursor.
[0126] Anhydrous ferric phosphate and lithium carbonate are mixed according to n(Fe):n(Li)=1:1.05.
[0127] The second carbon source solution is a glucose aqueous solution with a concentration of 20 wt %.
[0128] The feed ratio of the material and the second carbon source solution is 10g:7.5g.
[0129] The pressure of the air flow is 1±0.1 MPa; the air flow temperature is 100° C. when the material is mixed with the second carbon source solution, and the mixing time is 15 min.
[0130] The atomization pressure is 1MPa.
[0131] (3) The precursor is placed in a rotary kiln for calcination under a nitrogen atmosphere, and then mechanically crushed, sieved, and demagnetized to obtain a lithium iron phosphate positive electrode material. Calcination conditions: heating at 2°C / min to 700°C and keeping at this temperature for 8h.
[0132] Combining the product and preparation method of the present invention, as well as the product performance in Tables 1 to 3 above, it can be seen that in method embodiment 2, since anhydrous ferric phosphate is mixed with lithium acetate, titanyl sulfate, the first carbon source, the second carbon source, and the third carbon source by dry mixing, the agglomeration degree of the product prepared at this time is significantly higher than that of other method embodiments, which leads to lower compaction density and peel strength, larger standard deviation of surface density samples and electrode resistance samples, and poor rate performance and cycle stability. While method embodiment 3 changes the reaction parameters within the scope of the present invention, it still obtains good results. In method embodiment 4, since the first carbon source is not added, compared with embodiment 1, its The standard deviation of the surface density sample and the standard deviation of the electrode resistance sample are both low, and the specific capacity of the material is slightly reduced, but it is still significantly better than that of comparative examples 1-4, which fully proves that the carbon source of the present invention can achieve better results when there are only two. Method Example 5 adjusts the type and amount of the carbon source and the reaction conditions, and it can still obtain good performance. In Method Example 6, all raw materials are directly ball-milled and mixed, which will result in the FSSS and Method Example 7 was prepared according to the method of Method Example 5 with a chemical composition similar to that of Method Example 6. However, due to the The degree of agglomeration is better than that of method embodiment 6, so its comprehensive performance is better.
[0133] Comparative Examples 1 and 2 prepare lithium iron phosphate powder according to conventional methods, and then mix with a carbon source and calcine. Regardless of whether it is a one-stage calcination or a three-stage calcination, the comprehensive performance of the prepared lithium iron phosphate positive electrode material is significantly worse than that of the above-mentioned method embodiment. Compared with method embodiment 1, step (3) of comparative example 3 adopts a one-stage calcination, and its effect is significantly worse than that of method embodiment 1; the effect of comparative example 4 is worse than that of comparative example 3, which is based on the fact that only one carbon source is added. At this time, the prepared lithium iron phosphate positive electrode materials FSSS and Significantly improved, % and agglomeration degree are beyond the scope of this application, resulting in a significant decrease in the electrical performance of the product.
[0134] In addition, the present invention also provides method examples 8-14 and method comparative example 5, and method examples 8-14 and method comparative example 5 perform single factor variable analysis on a certain parameter of method example 1.
[0135] Specifically, the specific steps of method examples 8-14 and method comparative example 5 are as follows: Method Example 8 The difference from method example 1 is that the carbon source and the material are dry mixed in a ball mill, which includes the following steps: Anhydrous ferric phosphate with a Dv50 of 8.52 μm is mixed with lithium carbonate, a first carbon source, a second carbon source, and a third carbon source to obtain a material, and the material is put into a ball mill for grinding and crushing to obtain a precursor, and the Dv50 of the precursor is controlled to be 0.4~0.5 μm.
[0136] Anhydrous ferric phosphate and lithium carbonate are mixed according to n(Fe):n(Li)=1:1.05.
[0137] The first carbon source is polyimide; the second carbon source is glucose; and the third carbon source is ethylene glycol.
[0138] The total mass of anhydrous ferric phosphate and lithium carbonate, the feeding ratio of the first carbon source, the second carbon source and the third carbon source is 10g:0.5g:0.5g:0.5g.
[0139] Ball milling conditions: frequency is 30 Hz, 1 mm zirconia beads are used for ball milling, the volume ratio of the beads to the material is 1:1, the rotation speed is 600 rpm, the ball milling time is 3 h, and the temperature is room temperature.
[0140] The precursor is calcined in the same manner as step (3) of method example 1.
[0141] Method Example 9 The difference from method example 1 is that the carbon source and the material are mixed together in a pneumatic crushing device, comprising the following steps: (1) Same as method example 1 (2) preparing a carbon source mixed solution, wherein the mass percentages of polyimide, glucose, ethylene glycol, and solvent DMF are 10%:10%:10%:70% respectively; mixing the anhydrous iron phosphate obtained in step (1) with lithium carbonate as a material, and introducing the atomized carbon source mixed solution into an air flow pulverizing device with air as a medium to pulverize and coat the material to obtain a precursor.
[0142] Anhydrous ferric phosphate and lithium carbonate are mixed according to n(Fe):n(Li)=1:1.05.
[0143] The feed ratio of the material and the carbon source mixed solution is 10g:5g.
[0144] The pressure of the air flow is 1±0.1 MPa; the air flow temperature is 120° C. when the material and the carbon source mixed solution are mixed, and the mixing time is 20 min.
[0145] The atomization pressure is 1MPa.
[0146] (3) Same as method example 1.
[0147] Method Example 10 The difference from method example 1 is that the atomized third carbon source solution, the second carbon source solution and the first carbon source solution are introduced into the air flow pulverizing device in sequence to pulverize and coat the materials to obtain the first precursor, the second precursor and the third precursor respectively.
[0148] Method Example 11 The difference from method example 1 is that in step (2), the feed ratio of the material, the first carbon source solution, the second carbon source solution, and the third carbon source solution is 10 g: 8 g: 2.5 g: 2 g.
[0149] Method Example 12 The difference from method example 1 is that in step (2), the feed ratio of the material, the first carbon source solution, the second carbon source solution, and the third carbon source solution is 10 g: 2 g: 2.5 g: 8 g.
[0150] Method Example 13 The difference from method example 1 is that in step (2), the material and the carbon source solution are mixed at room temperature of 25°C.
[0151] Method Example 14 The difference from method example 1 is that a ball mill is used instead of an air flow mill to perform wet mixing. The specific steps are as follows: (1) Same as in method embodiment 1; (2) The anhydrous ferric phosphate obtained in step (1) is mixed with lithium carbonate as a material to prepare a first carbon source solution, a second carbon source solution and a third carbon source solution; the atomized first carbon source solution is sprayed onto the material in a stirring state, and after stirring, the material is placed in a ball mill for a first ball milling to obtain a first precursor; the atomized second carbon source solution is sprayed onto the first precursor in a stirring state, and after stirring, the material is placed in a ball mill for a second ball milling to obtain a second precursor; the atomized third carbon source solution is sprayed onto the second precursor in a stirring state, and after stirring, the material is placed in a ball mill for a third ball milling to obtain a third precursor; Anhydrous ferric phosphate and lithium carbonate were mixed at n(Fe): n(Li)=1:1.05. The atomization pressure was 1 MPa.
[0152] The first carbon source solution is a polyimide DMF solution with a concentration of 10 wt %; the second carbon source solution is a glucose aqueous solution with a concentration of 20 wt %; and the third carbon source solution is an ethylene glycol ethanol solution with a concentration of 10 wt %.
[0153] The feed ratio of the material, the first carbon source solution, the second carbon source solution and the third carbon source solution is 10g:5g:2.5g:5g.
[0154] Ball milling conditions: frequency is 30 Hz, 1 mm zirconia beads are used for ball milling, the volume ratio of the beads to the material is 1:1, and the rotation speed is 600 rpm; the ball milling temperature of the first ball mill is 120°C and the time is 1 h; the ball milling temperature of the second ball mill is 100°C and the time is 1 h; the ball milling temperature of the third ball mill is 80°C and the mixing time is 1 h.
[0155] (3) Same as method example 1.
[0156] Method Comparative Example 5 The difference from method example 1 is that only the second carbon source solution is added in step (2).
[0157] The products of the above method examples 8-14 and method comparative example 5 were tested, and the test results are shown in Table 4.
[0158] Table 4. Parameter detection statistics of different samples
[0159] As can be seen from the table above, in method example 8, anhydrous ferric phosphate is mixed with lithium carbonate, the first carbon source, the second carbon source, and the third carbon source and ball-milled to obtain a precursor. At this time, the FSSS and The FSSS was significantly increased, resulting in an increased degree of agglomeration and exceeding the scope of the present invention. In method example 9, all carbon sources were mixed together without being added sequentially, which would result in a slight increase in FSSS. , ρ% and agglomeration degree N are still within the preferred range of the present application. The order of adding carbon sources in method example 10 is opposite to that in method example 1. In this case, FSSS is slightly increased, but , ρ% and agglomeration degree N are still within the preferred range of the present application. In method examples 11-12, the amounts of the first carbon source, the second carbon source and the third carbon source added are adjusted. It can be seen that the changes in the amounts of the first carbon source and the third carbon source added will also have a certain impact on the product performance parameters. Among them, when the amount of the first carbon source increases and the amount of the third carbon source decreases, FSSS increases and BET decreases. , ρ% and agglomeration degree N increase. When the amount of the first carbon source decreases and the amount of the third carbon source increases, FSSS decreases and BET increases. , and the degree of agglomeration N are reduced. Therefore, the above parameters can be controlled within a reasonable range by adjusting the amount of carbon source added. In method example 13, the mixing temperature of the material and the carbon source solution is changed, and the obtained The results are significantly increased and exceed the preferred range of the present invention. In method embodiment 14, a ball mill is used instead of an air flow mill to perform wet mixing. It can be seen that both air flow milling and ball milling can be used to prepare the mixture. and In a specific range of lithium iron phosphate positive electrode materials, the materials are mixed by air flow milling, which can make the dispersion of the components in the precursor better, and the carbon source is evenly dispersed on the surface of anhydrous iron phosphate or lithium source particles, which is conducive to subsequent uniform gasification and pore formation, and obtains lithium iron phosphate positive electrode materials with uniform carbon material distribution. Through the above method embodiments, it can be seen that by adjusting within the parameter range of the present invention, it can be obtained to simultaneously meet and In a specific range of lithium iron phosphate positive electrode materials, this lithium iron phosphate positive electrode material has good dispersibility, low degree of agglomeration and high compaction density. The positive electrode sheet prepared therefrom has the characteristics of uniform surface density and high peeling strength. Therefore, the prepared battery has higher specific capacity and cycle stability.
[0160] However, in comparative example 5, only the second carbon source is added, which will result in FSSS exceeding the scope of the present invention. The concentration of carbon in the lithium phosphate cathode material increased significantly, and finally resulted in the degree of agglomeration exceeding the scope of the present invention, which fully proved that it was impossible to obtain a lithium iron phosphate cathode material with a degree of agglomeration lower than 25,000 by adding only one carbon source.
[0161] The present invention also conducted electron microscope scanning on the products of the above-mentioned Example 1, Example 8 and Comparative Example 4. Please refer to the SEM images. Figure 1 , Figure 2 and Figure 3 .
[0162] from Figure 1 , Figure 2 and Figure 3 From the comparison, it can be seen that the dispersibility is: Example 1> Example 8> Comparative Example 4.
[0163] Furthermore, the present invention also conducted Raman spectroscopy tests on the lithium iron phosphate cathode materials provided in Example 1 and Example 4: the graphitization degree of the lithium iron phosphate cathode materials was characterized using a German Burker RFS100 / S Raman spectrometer, with an excitation wavelength of 458 nm, and a Gaussian function was used for fitting after back-blinding, 1300~1400cm -1 The corresponding D band characteristic peak represents the A of sp³ hybridized carbon atoms. 1g Vibration reflects the defects or disordered structure of carbon materials, and the corresponding peak intensity is I D ; 1500~1600cm -1 The corresponding G band characteristic peak represents sp 2 Hybridized carbon atom E 2gVibration reflects the ordered structure of carbon materials, and the corresponding peak intensity is I G ,by Evaluate the graphitization degree of carbon materials in lithium iron phosphate cathode materials. Figure 4 .
[0164] Since the higher the graphitization degree, the better the conductivity of the carbon material. Figure 4 , I of Example 1 G / I D =1.22, I of Example 4 G / I D =1.09, indicating that adding the first carbon source is beneficial to improving the graphitization degree of the lithium iron phosphate positive electrode material. Moreover, the carbon source feed amount of method embodiment 4 is greater than that of method embodiment 1, but the carbon material content of embodiment 1 is higher, indicating that adding the first carbon source is beneficial to increasing the solid residue of the carbon source, thereby increasing the conductive carbon.
[0165] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium iron phosphate positive electrode material, characterized in that: It includes primary particles and secondary particles, wherein the secondary particles are formed by agglomeration of primary particles, and the lithium iron phosphate positive electrode material satisfies =5~40 and ρ%=50%~90%, wherein the FSSS refers to the Feasibility Study particle size of the lithium iron phosphate positive electrode material, in μm; the D BET It refers to the specific surface area particle size of the lithium iron phosphate positive electrode material, in μm; ρ%=1-H%, ρ% refers to the relative density of the secondary particles, and H% refers to the porosity of the secondary particles.
2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The D BET is the particle size of the lithium iron phosphate positive electrode material measured and calculated by nitrogen adsorption-desorption method, , wherein the BET refers to the specific surface area of the lithium iron phosphate positive electrode material, and the value range of the BET satisfies ≤20m 2 / g, refers to the true density of the lithium iron phosphate positive electrode material, The value range of is 3.3~3.6 g / cm³; And / or, the FSSS is the average particle size of the lithium iron phosphate positive electrode material measured by a steady-flow air permeation method, and the value range of the FSSS satisfies 0.4-5 μm; And / or, the agglomeration degree N of the lithium iron phosphate positive electrode material is less than 25000, wherein the agglomeration degree ; And / or, the compaction density of the lithium iron phosphate positive electrode material is 1.9-3.0 g / cm 3 .
3. The lithium iron phosphate positive electrode material according to claim 2, characterized in that: The lithium iron phosphate positive electrode material satisfies =10~30; And / or, the secondary particles of the lithium iron phosphate positive electrode material satisfy ρ%=50%~70%; And / or, the lithium iron phosphate positive electrode material satisfies a degree of agglomeration N of 200 to 12000; And / or, the lithium iron phosphate positive electrode material satisfies FSSS=1~2.5μm; And / or, the lithium iron phosphate positive electrode material satisfies the BET range of 9 to 15 m 2 / g.
4. The lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The lithium iron phosphate positive electrode material comprises an active material matrix and a carbon material. The general formula of the active material matrix is Li 1-x A x Fe 1-y M y (PO 4-z )D z , wherein A is selected from one or more of Na and Mg; M is selected from one or more of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D is selected from one or more of F, S, N and Cl; 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.1; the mass of the carbon material is 1%~5% of the mass of the lithium iron phosphate positive electrode material.
5. A method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: It includes: Mixing iron phosphate and lithium salt as materials, and mixing the materials with carbon sources having different gasification temperatures to obtain a precursor; The precursor is calcined in stages under an inert atmosphere, and then crushed, sieved, and demagnetized to obtain a lithium iron phosphate positive electrode material.
6. The method for preparing the lithium iron phosphate positive electrode material according to claim 5, characterized in that: The step of mixing the iron phosphate and the lithium salt comprises at least one of characteristics I to IV; Feature I: Before the iron phosphate is mixed with the lithium salt, the iron phosphate is first added to a gas flow pulverizing device for pulverization; Feature II: The lithium salt is at least one of lithium carbonate, lithium oxalate and lithium acetate; Feature III: When the iron phosphate and the lithium salt are mixed, a dopant is further added, wherein the dopant is at least one of a salt, an oxide and a hydroxide of a doping element; Feature IV: The iron phosphate and the dopant are added according to a stoichiometric ratio.
7. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The carbon sources with different gasification temperatures include a first carbon source with a gasification temperature of 400-600°C, a second carbon source with a gasification temperature of 200-400°C, and a third carbon source with a gasification temperature of 100-200°C; The first carbon source comprises at least one of polyimide, polyphenylene ether and polyetherimide; The second carbon source comprises at least one of glucose, polyethylene glycol, starch, sucrose, maltose, cellulose, chitosan, polyacrylonitrile, benzyl alcohol and glycerol; The third carbon source includes at least one of phenol, ethylene glycol, propylene glycol, butylene glycol, isopropanol, sorbitol, erythritol, fructose, malic acid, citric acid and salicylic acid.
8. The method for preparing a lithium iron phosphate positive electrode material according to claim 7, characterized in that: The step of mixing the material with carbon sources having different gasification temperatures comprises at least one of features V to IX; Feature V: The material and the carbon source with different gasification temperatures are mixed in a gas flow milling device, and a gas flow is introduced during the mixing, the pressure of the gas flow is 0.5-1.5 MPa, and the temperature is 25-120° C.; the total mixing time is 15-60 min; Feature VI: Before the carbon sources with different gasification temperatures are mixed with the material, they are first prepared into a carbon source solution with a mass percentage concentration of 10% to 30%, and then the carbon source solution is atomized and then mixed with the material, wherein the atomization pressure is 0.1 to 1.5 MPa; Feature VII: The material is first mixed with the first carbon source, then mixed with the second carbon source, and finally mixed with the third carbon source; Feature VIII: The total mass of the carbon sources with different gasification temperatures is 15% to 25% of the mass of the material; Feature IX: When the material is mixed with carbon sources having different gasification temperatures, the mass ratio of the first carbon source, the second carbon source and the third carbon source is 0~15:2.5~15:2.5~10.
9. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The staged calcination includes a first stage, a second stage and a third stage. The first stage is heated to 180-220°C at a speed of 1-2°C / min and kept warm for 1-2 hours; the second stage is heated to 380-420°C at a speed of 2-3°C / min and kept warm for 2-4 hours; the third stage is heated to 650-750°C at a speed of 4-6°C / min and kept warm for 4-8 hours.
10. A lithium ion battery, characterized in that: It includes the lithium iron phosphate positive electrode material as described in any one of claims 1 to 4 or the lithium iron phosphate positive electrode material prepared by the preparation method of the lithium iron phosphate positive electrode material as described in any one of claims 5 to 9.
Citation Information
Patent Citations
Lithium iron phosphate having an olivine structure, and preparation method thereof
CN102186768A
Preparation method of carbon / carbon nanotube coated lithium iron phosphate composite material by in situ synthesis
CN106876705A
Preparation method for dual-carbon-source-coated lithium iron phosphate material
CN107069005A
Fluorine-doped porous lithium ferric manganese phosphate, preparation method thereof, positive electrode and battery
CN116443842A
Preparation method of lithium iron phosphate aggregate positive electrode material with high mechanical strength and high density
CN117208876A
Cited By
Iron phosphate and preparation method thereof
CN120943229A
Lithium iron phosphate positive electrode material and preparation method therefor, and lithium-ion battery
WO2026144459A1